Penerjemahan Idiom Bahasa Inggris dalam Film Angel Has Fallen - Riswantika, Mita Rachma; Ikrarini, Estri Oktarena; Hikmah, Isti’anatul (Jurnal Penerjemahan, 2022)
The study aims to find out and describe the strategies used in translating idioms and equivalence applied in the translation of subtitle text of Angel Has Fallen movie. The research used the descriptive qualitative method. The data were in the form of words and sentences. This study was qualitative research in which the data were collected from the translation of the subtitle text of Angel Has Fallen movie. After the data had been collected, the researcher analyzed the strategies used in translating idioms and equivalence. The results of this study are 1) five out of six strategies in translation idioms found in the data namely using an idiom of similar meaning and form, using an idiom of similar meaning but dissimilar form, translation by paraphrase, translation by omission of a play on idiom, and translation by omission of entire idiom and 2) All of two kinds of equivalence found in the data; formal and dynamic equivalence.Keywords: idiomatic translation strategies, movie subtitle, equivalence